Use of volumetric CT scanning to predict tumor staging and survival in pancreatic cancer patients that are to be administered curative resection. Issue 8 (8th March 2021) - Sengul Samanci, Nilay; Çelik, Emir; Bagcilar, Omer; Tutar, Onur; Samanci, Cesur; Velidedeoglu, Mehmet; Yassa, Ahmet Ersin; Demirci, Nebi Serkan; Demirelli, Fuat Hulusi
Abstract: Background: This study evaluates the achievability of CT volumetry of pancreatic cancer and its correlation with pTNM stage and survival. Methods: Tumor volume was measured from contrast enhanced CT images of 58 patients who undergo curative resection for pancreatic cancer using the Segment Editor module implemented in 3D‐Slicer—a free open source software platform. Receiver operating characteristic (ROC) analysis was used to evaluate correlation between Tvol and pTNM staging. Results: The preoperative images of 58 pancreatic adenocarcinoma patients were included. The mean Tvol of pancreatic cancer is an increasing trend with T stage (The mean T1vol = 1.75 cm 3, the mean T2vol = 11.43 cm 3, the mean T3vol = 14.98 cm 3, the mean T4vol = 19.6 cm 3 ). There were statistical differences between volumes ( p = .000). On ROC analysis, the area under the ROC curve (Az) of Tvol to differentiate T1 stage from ≥T2 stage was 0.966 ( p = .000). At a cut‐off value of 3.050 cm 3, sensitivity of 92.3%, and specificity of 83.3% were achieved. Az value of Tvol to differentiate ≤T2 from ≥T3 stage was 0.750 ( p = .010). At a cut‐off value of 10.250 cm 3, sensitivity of 72.7% and specificity of 66% were achieved. In addition Az value of Tvol to differentiate ≤T3 from ≥T4 stage was 0.652 and was not significant ( p = .380). At a cut‐off value of 11.2 cm 3, sensitivity of 66.7% and specificity of 63.6% were achieved. Conclusion: CT volumetry in pancreatic cancer is feasible with excellent reproducibility. It is one of the prognostic factors affecting survival in operated patients with pancreatic cancer.